PTU-149 Barrett's Oesophagus Patients Attending Hospital: Baseline Clinical, Patient History and Quality of Life Data from Boss and Aspect. (17th August 2016) - Love, S; Reilly, G; Roberts, C; Moayyedi, P; Foy, C; Stokes, C; De Caestecker, J; Attwood, S; Watson, P; Ang, Y; Bhandari, P; Old, O; et al.
Abstract : Introduction: From 2005 to 2011 two large UK studies recruited 6, 327 evaluable patients with Barrett's Oesophagus attending hospital clinics. Baseline clinical, patient history and quality of life data was collected prior to randomisation and this rich dataset is the basis for this abstract. Methods: Patients were recruited to AspECT and BOSS at local centres through normal endoscopy clinics and surveillance lists including those newly diagnosed or with an existing diagnosis of Barrett's oesophagus. Baseline information was collected on age, gender, ethnicity, length of Barrett's, presence of hiatus hernia, intestinal metaplasia and low grade dysplasia, concomitant medications, comorbidities, duration and severity of symptoms and patients' self-reported Quality of Life data. Results: The sample was mainly male (75%, n = 6, 327) with median age of 64 years (range 18–92 years, n = 6, 327). Median Barrett's length was 4 cm (range 1–24 cm, n = 6, 029) and median time since diagnosis of Barrett's was 2 years (range 0–41 years, n = 5, 805). At least one symptom of reflux was experienced by 60% of patients and 46% of patients experienced at least one symptom at least once per week (n = 1, 072). Length of Barrett's was associated with age (n = 6, 029), gender (n = 6, 029), presence of low grade dysplasia (n = 5, 955), presence of intestinal metaplasia (n = 6, 026) and time since diagnosis (n = 5, 913). Conclusion: This is our first release of data from AspECT and BOSS with more to follow. It is a large set of data on Barrett's patients which we expect to be typical of Barrett's patients attending hospital clinics in the UK. The average person was a male age 62 with 4 cm Barrett's having had a Barrett's diagnosis for 2 years. Acknowledgements: Our thanks to the patients and the sites. AspECT is sponsored by the University of Oxford with grant funding from CR-UK (A4584) and support from the Investigator-Sponsored Study Program of AstraZeneca with trial management provided by OCTO. BOSS is funded by the HTA grant number HTA 05/12/01 with trial management provided by BOSS trial office Gloucestershire Hospitals NHS Trust. The Centre for Statistics in Medicine provides statistical input to both AspECT and BOSS. Disclosure of Interest: None Declared